Practical guide to structuring the Background section in clinical and epidemiological studies - Charlotte Leboeuf-Yde; Claire Gudex (Chiropractic & Manual Therapies, 2026)
Abstract This is the first of three articles that provide step-by-step guides on how to structure the content of a scientific article to ensure a coherent and relevant text. This article deals with the Background section, with extra focus on the research objectives. We introduce the four typical elements of a Background section: (i) justification of the study topic, (ii) sufficient information for the reader to understand the research project, (iii) presentation of the research gaps that justify the research objectives, and (iv) well-constructed research objectives that indicate the study design and may include a purpose statement. Because the whole text is driven by the research objectives, we first suggest some tips for making these as informative as possible. We then provide a step-by-step approach for planning the structure and contents of the Background section as preparation for writing the full text later. We illustrate our explanations with text examples selected from this journal to show how authors have approached crucial aspects of the Background section. Finally, we discuss some pros and cons of using artificial intelligence during the writing process, and how its use can be reported. We hope that this practical guide to the structuring process will provide authors with a useful framework for the later addition of the full text and relevant references.